Short-terme effects of elastic taping on gymasts jumping performance - Vinken, P. M. (Science of Gymnastics Journal, 2015)
It was explored whether three different applications of elastic tape on the lower limbs of active, healthy gymnasts influence their vertical jumping performance. 16 gymnasts randomly performed drop jumps, squat jumps, and counter movement jumps on a force platform in four experimental conditions: 1. no tape application, 2. rectus femoris tape application, 3. triceps surae tape application, and 4. sham tape application. Five task-relevant parameters were calculated in order to represent vertical jumping performance in the three vertical jumping tasks: